Experimental and numerical investigations of water entry in subsea modules with porous structures. (April 2021) - Zan, Yingfei; Guo, Ruinan; Yuan, Lihao; Ma, Qingwei; Zhou, Ao; Huang, Fuxiang; Jia, Hui
Highlights: l Good agreement between experimental and CFD results for content velocity tests. l The influence of porous structures was quantified using proposed CFD method. l The effects of vertical velocity on slamming time, impact duration and impulse and were discussed. Abstract: Slamming impacts on subsea modules used for oil and gas exploration and production have become an increasingly important structural safety issue. There are many aspects of the subsea module water entry problem that have not yet been sufficiently explored, and these include the shape of the module and its impact velocity. In this study, a large-scale model and computational fluid dynamics (CFD) simulations were used to explore these aspects, with a focus on their role in porous plates. The numerical simulation results for vertical forces showed good agreement with the experimental results. The CFD simulations, numerical methods, and computing grids can be used to accurately and efficiently determine the slamming loads both in the time domain and at specified points. The critical vertical speed snap load was 0.093 m/s for the studied module. The air layer under the porous plates plays an important role in the slamming impact. The maximum delay in slamming caused by the porous plates was 79% at a vertical speed of 0.1 m/s.